Design and fabrication of superhydrophobic membranes by electrospinning for direct contact membrane distillation - Liao, Yuan (2015)
Fast global population growth, serious environmental pollution and rapid economic developments have resulted in water scarcity around the world. Membrane distillation (MD) processes were considered as an attractive technology to treat waste water, recycle polluted water and provide more freshwater resources. This thesis provides a brief review on the research and developments of MD process, commercial MD membranes and lab-fabricated MD membranes. As the electrospun composite nanofibrous membranes have great potential to be used in MD due to their unique structural features, the complex electrospinning process has also been reviewed, including the materials and operating parameters which could control nanofiber formation, and various designs of electrospun apparatus which can produce nanofiber membranes with different appearances. However, it is found that limited works have been carried out to fabricate MD membranes by electrospinning. In this work, poly (vinylidene fluoride) (PVDF) nanofiber membranes were fabricated through electrospinning for direct contact membrane distillation (DCMD) as a first trial. The effects of PVDF dope concentration, inorganic salt additives, sprayer’s moving speed, and chamber moisture on the properties of resultant membranes were investigated. It also illustrates the importance of processing parameters and heat-press post-treatment, and demonstrates that the heat-press post-treatment improved membrane integrity significantly and enhanced permeate flux in DCMD process. All the electrospun nanofiber membranes possessed high water contact angles (between 135° to 142°) due to their high surface roughness. The post-treated PVDF nanofiber membranes were able to present a steady water permeation flux of 21 kg m-2h-1 throughout the entire testing period of 15 h, using a 3.5 wt% NaCl solution as the feed under the feed and permeate inlet temperatures of 323 K and 293 K, respectively. However, PVDF nanofiber membranes without hydrophobic additives or surface modification do not have sufficient anti-wetting performance. Further treatment of PVDF nanofiber should be carried out to impart them with better wetting resistance and long-term stability. Two types of superhydrophobic PVDF nanofiber membranes, integrally-modified and surface-modified PVDF membranes, have been successfully fabricated by electrospinning followed by surface modification, which includes dopamine surface activation, silver nanoparticle deposition and hydrophobic treatment. The modification is convenient because of mild reactions and wide applicability. The characterizations revealed that the modifications have altered the membrane surface morphology and topology, and made the membrane superhydrophobic due to their hierarchical structures. Compared with unmodified membrane, the integrally-modified membrane (I-PVDF) can achieve a high and stable MD water flux of 31.6 kg m-2h-1 using a 3.5 wt% NaCl as the feed solution while the feed and permeate temperatures were fixed at 333 K and 293 K, respectively. To the best of our knowledge, this result is superior to all other PVDF flat sheet membranes tested under the same or similar conditions, which is believed to be attributed to the open surface pore structure and the thin thickness of the PVDF nanofiber membrane with the aid of electrospinning. The superhydrophobic nature of the membrane surface brought by the integral modification on all nanofibers renders the membrane anti-wetting property while remaining high water flux. Moreover, inspired by the unique structure of lotus leaf, a novel strategy is developed to construct composite nanofiber membranes with robust superhydrophobicity and high porosity suitable for use in MD. The newly developed membrane consists of a superhydrophobic silica-PVDF composite selective skin formed on PVDF porous nanofiber scaffold via electrospinning. This fabrication method could be easily scaled up due to its simple preparing procedures. The effects of silica diameter on membrane contact angle, sliding angle and MD performance were investigated thoroughly. For the first time, the DCMD tests demonstrate that the newly developed membranes are able to present stable high performance over 50 h of testing time, and the superhydrophobic selective layer exhibits excellent durability in ultrasonic treatment and continuous DCMD test. It is believed that this novel design strategy has great potential for MD membrane fabrication. Additionally, to further improve the wetting repellent property of superhydrophobic membranes, 3-dimensional (3D) superhydrophobic membranes were developed as a possible solution. Moreover, since highly porous nanofiber membranes usually suffer from insufficient mechanical property, which have adverse impact on membrane packing in the module, thus, a dual-layer membrane was fabricated by electrospinning 3D superhydrophobic composite layers on a non-woven support to improve its wetting resistance and enhance mechanical robustness Another type of dual-layer superhydrophobic composite membranes consisting of PVDF nanofibrous support and an ultrathin 3D superhydrophobic selective layer was prepared to compare with the as-fabricated non-woven-supported superhydrophobic dual-layer membrane. All these membranes exhibit superhydrophobicity towards distilled water, salty water, oil-water mixture and beverages, which enables them to be used not only for desalination but also for other concentrating treatments. Compared with nanofiber-supported dual-layer membranes, the non-woven-supported membranes exhibit higher mechanical strength as a result of excellent combination with non-woven support and better long-term performance because of the thicker 3D superhydrophobic structure. The morphology, pore size, porosity, mechanical properties as well as liquid enter pressure of water of these superhydrophobic composite membranes and commercial PVDF membrane are measured and compared. The possible wetting procedures of the as-prepared superhydrophobic dual-layer membranes are also illustrated in this study. Finally, this thesis provides some personal perspectives for the future developments in which the composite nanofiber membranes could be pursued for water research. In conclusion, this thesis presents the design and development of novel superhydrophobic nanofiber membranes based on the studies of the fundamental mechanisms of electrospinning, surface modification on nanofiber membranes, fabrication of robust superhydrophobic membranes, and preparation of 3D superhydrophobic dual-layer membrane. This work contributes to the development of membrane fabrication technology and facilitates the practical applications of membrane distillation process.